Cerebrospinal α‐Synuclein Oligomers Reflect Disease Motor Severity in DeNoPa Longitudinal Cohort - Nour K. Majbour (8809316) (2023)
Background Tangible efforts have been made to identify biomarkers for Parkinson's disease (PD) diagnosis and progression, with α-synuclein (α-syn) related biomarkers being at the forefront. Objectives The objectives of this study were to explore whether cerebrospinal fluid (CSF) levels of total, oligomeric, phosphorylated Ser 129 α-synuclein, along with total tau, phosphorylated tau 181, and β-amyloid 1–42 are (1) informative as diagnostic markers for PD, (2) changed over disease progression, and/or (3) correlated with motor and cognitive indices of disease progression in the longitudinal De Novo Parkinson cohort. Methods A total of 94 de novo PD patients and 52 controls at baseline and 24- and 48-month follow-up were included, all of whom had longitudinal lumbar punctures and clinical assessments for both cognitive and motor functions. Using our in-house enzymelinked immunosorbent assays and commercially available assays, different forms of α-synuclein, tau, and β-amyloid 1–42 were quantified in CSF samples from the De Novo Parkinson cohort. Results Baseline CSF total α-synuclein was significantly lower in early de novo PD compared with healthy controls, whereas the ratio of oligomeric/total and phosphorylated/total were significantly higher in the PD group. CSF oligomeric-α-synuclein longitudinally increased over the 4-year follow-up in the PD group and correlated with PD motor progression. Patients at advanced stages of PD presented with elevated CSF oligomeric-α-synuclein levels compared with healthy controls. Conclusions Longitudinal transitions of CSF biomarkers over disease progression might not occur linearly and are susceptible to disease state. CSF oligomeric-α-synuclein levels appear to increase with diseases severity and reflect PD motor rather than cognitive trajectories. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Other Information Published in: Movement Disorders License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/mds.28611